ANALISIS PROXIMATE DAN NILAI KALOR BRIKET HYBRID (BROWN COAL – KULIT DURIAN) DENGAN PEREKAT LIQUID VOLATILE MATTER (LVM) YANG DI PREPARASI DENGAN METODE PIROLISIS - E.S. Hasan; M. Jahiding; J. Arsyad (Universitas Halu Oleo, 2017)
Research on briquette quality hybrid by proximate analysis, calorific value, and a flame test has been conducted. Briquettes hybrid made by using Liquid Volatile Matters (LVM) as the glue. The LVM was varied with the composition of 5%, 10%, 15% of the sample. Hybrid briquettes have a calorific value ranging between 5144,79kal / g - 6922.07 cal / g. Rising temperatures are also likely to affect the timing and duration of the test flame hybrid briquettes. The higher the pyrolysis temperature and adhesive composition Liquid Volatile Matters (LVM) the longer briquettes burning flame time.